2004
DOI: 10.1007/s00421-004-1070-0
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum leptin levels during prolonged high altitude exposure

Abstract: Circulating leptin concentrations are shown to be influenced not only by hormones, but also by body weight and energy balance. High altitude (HA) exposure induces a daily negative energy balance and stress hormone activation. The aim of our study was to evaluate leptin concentration during both acute and prolonged HA exposure and its correlations with some metabolic and hormonal parameters. Twelve males were studied during a stay at HA (15-20 days at 5,050 m). Blood samples for serum leptin, plasma insulin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 28 publications
2
42
2
Order By: Relevance
“…An increase in leptin coupled with ghrelin decrease has been described after acute exposure to HA (17,19), but other authors reported that prolonged HA exposure is associated with a reduction of leptin concentrations, likely due to the loss of body mass and the strong hypoxia-related sympathetic activation (18). These studies relied on single leptin and ghrelin measurements while we evaluated mean leptin and ghrelin concentrations over 2 h. Indeed, we found a nonsignificant trend toward decreased leptin levels, but ghrelin levels were completely unchanged despite the significant body weight loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increase in leptin coupled with ghrelin decrease has been described after acute exposure to HA (17,19), but other authors reported that prolonged HA exposure is associated with a reduction of leptin concentrations, likely due to the loss of body mass and the strong hypoxia-related sympathetic activation (18). These studies relied on single leptin and ghrelin measurements while we evaluated mean leptin and ghrelin concentrations over 2 h. Indeed, we found a nonsignificant trend toward decreased leptin levels, but ghrelin levels were completely unchanged despite the significant body weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the emerging role of leptin and ghrelin in the regulation of energy balance prompted an evaluation of leptin response to HA (17)(18)(19)(20). Subjects exposed to HA lose significant amounts of body mass from fat mass as well as fat-free mass, particularly if involved in physical performance such as climbing (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, hypoxia has been shown to clearly increase leptin gene expression in adipocyte studies (40). As suggested by Zaccaria et al (38), it therefore seems plausible that exposure to HA leads to a leptin increase, which causes a satiety signal to the brain contributing to anorexia and weight loss.…”
Section: Discussionmentioning
confidence: 85%
“…Published data have been somewhat inconsistent reporting an increase (12,37), a decrease (38), or no change (13,39) in leptin after ascent to HA. However, hypoxia has been shown to clearly increase leptin gene expression in adipocyte studies (40).…”
Section: Discussionmentioning
confidence: 98%